2016
DOI: 10.1159/000443882
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Francisella tularensis</i></b> Modulates a Distinct Subset of Regulatory Factors and Sustains Mitochondrial Integrity to Impair Human Neutrophil Apoptosis

Abstract: Tularemia is a disease characterized by profound neutrophil accumulation and tissue destruction. The causative organism, Francisella tularensis, is a facultative intracellular bacterium that replicates in neutrophil cytosol, inhibits caspase activation and profoundly prolongs cell lifespan. Here, we identify unique features of this infection and provide fundamental insight into the mechanisms of apoptosis inhibition. Mitochondria are critical regulators of neutrophil apoptosis. We demonstrate that F. tularensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 46 publications
7
61
0
Order By: Relevance
“…F. tularensis is another intracellular bacterial pathogen that delays neutrophil apoptosis by affecting Bcl-2 family proteins. Namely, the pathogen impairs the processing and activation of caspase-8 and Bid, and significantly inhibits apoptosis by impairing translocation of Bax into the mitochondria [56, 57]. More recently, it has been suggested that F. tularensis- secreted bacterial lipoproteins play a role in apoptosis inhibition via a TLR-2 dependent route [58].…”
Section: Bacterial Strategies To Evade Neutrophil Functionmentioning
confidence: 99%
“…F. tularensis is another intracellular bacterial pathogen that delays neutrophil apoptosis by affecting Bcl-2 family proteins. Namely, the pathogen impairs the processing and activation of caspase-8 and Bid, and significantly inhibits apoptosis by impairing translocation of Bax into the mitochondria [56, 57]. More recently, it has been suggested that F. tularensis- secreted bacterial lipoproteins play a role in apoptosis inhibition via a TLR-2 dependent route [58].…”
Section: Bacterial Strategies To Evade Neutrophil Functionmentioning
confidence: 99%
“…The importance of microbial virulence factors is nicely illustrated in an article by Blaschke et al [25], in which they show that cytolysins of the important bacterial pathogen Streptococcus pyogenes induce the expression of cyclooxygenase 2, resulting in proinflammatory activities. The importance of the resolution of inflammation to avoid excessive tissue damage, but also from the microbial side to avoid eradication, illustrates the dichotomy of host responses [8,10,26,27,28]. We hope that you will find this issue of Journal of Innate Immunity interesting and thought provoking!…”
mentioning
confidence: 96%
“…The same applies for the Chemistry Prize. Electron microscopy is an essential tool when studying innate immunity [6,7,8,9,10,11]. It will therefore be exciting to see how the new developments will advance the forthcoming research outcome.…”
mentioning
confidence: 99%
“…Francisella tularensis is an aerobic rod-shaped Gram-negative pathogen that can sustain mitochondrial integrity, thereby delaying apoptosis in neutrophils [9]. In this issue Ireland et al [10] show that phospholipids derived from F. tularensis act as immunomodulatory substances, executing anti-inflammatory activity.…”
mentioning
confidence: 99%